Sonographic abnormality of the substantia nigra in melanoma patients. Issue 2 (31st October 2012) - Rumpf, Jost‐Julian; Weise, David; Fricke, Christopher; Wetzig, Tino; Simon, Jan‐Christoph; Classen, Joseph
<x xml:space="preserve">Abstract</x> Background Evidence derived from large epidemiological studies suggests an association between Parkinson's disease (PD) and malignant melanoma. Transcranial sonography of the midbrain reveals an extended echogenic substantia nigra (SN) area in a high proportion of patients with PD. This characteristic, in the context of PD, may signal degeneration of dopaminergic nigrostriatal projection neurons. Demonstration of an increased prevalence of abnormal echogenic SN in melanoma patients could add weight to the hypothesis of an underlying common pathogenic pathway of both diseases. Methods This was a cross‐sectional observational study. Transcranial sonography of the SN region was performed on 31 patients suffering from malignant melanoma and 29 healthy participants. In addition, patients and controls were screened for motor and non‐motor symptoms of PD. Results The echogenic SN area was abnormally extended in 42% of melanoma patients versus 7% of control subjects (χ2= 9.811, P = .002). Mean echogenic SN area (SN[R, L]) was significantly larger in melanoma patients than in controls (patients, 0.21 ± 0.07 cm2; controls, 0.15 ± 0.04 cm2 [mean ± SD]; unpaired t test, P < .001). Conclusions These findings provide additional evidence in favor of a common pathogenic pathway of PD and malignant melanoma and raise the possibility that their association is closer than previously assumed. © 2012 Movement Disorder Society